Development and Validation of Novel Dietary and Lifestyle Inflammation Scores. Issue 12 (2nd August 2019) - Byrd, Doratha A; Judd, Suzanne E; Flanders, W Dana; Hartman, Terryl J; Fedirko, Veronika; Bostick, Roberd M
ABSTRACT: Background: Chronically higher inflammation, which may partly result from diet and lifestyle, is implicated in risk for multiple chronic diseases. The dietary inflammatory index (DII) and empirical dietary inflammatory pattern (EDIP), developed to characterize dietary contributions to systemic inflammation, have several limitations. There are no scores to characterize contributions of lifestyle to inflammation. Objectives: To reflect dietary/lifestyle contributions to inflammation, we developed novel, inflammation biomarker panel-weighted, dietary (DIS) and lifestyle (LIS) inflammation scores in a subset ( n = 639) of the Reasons for Geographic and Racial Differences in Stroke Study (REGARDS) cohort. Methods: We selected a priori 19 food groups and 4 lifestyle characteristics to comprise the DIS and LIS, respectively. We calculated the components' weights based on their strengths of association with an inflammation biomarker score [comprising high-sensitivity C-reactive protein (hsCRP), IL-6, IL-8, and IL-10] using multivariable linear regression. The sums of the weighted components constitute the scores, such that higher scores reflect, on balance, more proinflammatory exposures. We calculated the DIS, LIS, DII, and EDIP with cross-sectional data from the remaining REGARDS cohort ( n = 14, 210 with hsCRP measurements) and 2 other study populations with hsCRP and/or an 8-component inflammation biomarker panel, and investigated their associations with circulating inflammation biomarker concentrations using multivariable logistic regression. Results: In REGARDS, those in the highest relative to the lowest DIS, LIS, DII, and EDIP quintiles had statistically significant 1.66-, 4.29-, 1.56-, and 1.32-fold higher odds of a high hsCRP concentration (>3 mg/dL), respectively (all P -trend < 0.001). Those in the highest relative to the lowest joint DIS/LIS quintile had a statistically significant 7.26-fold higher odds of a high hsCRP concentration. Similar findings were noted in the other 2 validation populations. Conclusion: Our results support that dietary and lifestyle exposures collectively contribute substantially to systemic inflammation, and support the use of our novel DIS and LIS.